17.1k views
3 votes
Simplify each expression by distributing and combined bf like terms (SHOW WORK) please

Simplify each expression by distributing and combined bf like terms (SHOW WORK) please-example-1
User Axnsan
by
5.4k points

1 Answer

3 votes

Answer:

c - 39

Explanation:

Given,

-4 (8 - c ) - (3c + 7 )

= -4 ( -c + 8 ) - (3c + 7 )

= 4c - 32 - ( 3c + 7 )

= 4c - 32 - 3c - 7

= ( 4 - 3 )c + ( -32 - 7 )

= c + ( -32 - 7)

= C - 39

hope this answer helps you dear! take care!

User Shereef Marzouk
by
6.3k points